2017
DOI: 10.1007/s11010-017-3040-y
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate protects BEAS-2B cells from lipopolysaccharide-induced apoptosis through upregulation of gastrin-releasing peptide

Abstract: Gastrin-releasing peptide (GRP) plays a major role in the development and maintenance of lung epithelial cells by promoting cell division, whereas its suppression causes growth arrest and apoptosis. The present study shows that human bronchial epithelial BEAS-2B cells challenged with lipopolysaccharide (LPS), an endotoxin from gram-negative bacteria, downregulated GRP expression and induced apoptosis via upregulation of p53 and active caspase-3, signifying the importance of GRP in lung epithelial cell survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Similarly, following the establishment of CVA models, we found that treatment with amygdalin at lower than 400 μg/mL promoted the toxicity of CVA model cells. Besides, both airway epithelial inflammation and dysfunction in allergic asthma and exposure to LPS were found to induce cell apoptosis [29,30]. Analogously, our study demonstrated an apoptosis-inducing effect of LPS.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, following the establishment of CVA models, we found that treatment with amygdalin at lower than 400 μg/mL promoted the toxicity of CVA model cells. Besides, both airway epithelial inflammation and dysfunction in allergic asthma and exposure to LPS were found to induce cell apoptosis [29,30]. Analogously, our study demonstrated an apoptosis-inducing effect of LPS.…”
Section: Discussionsupporting
confidence: 77%
“…The human bronchial epithelial cell line BEAS-2B (CRL-9609), the human broblast cell line IMR90 (CCL-186), and the human lung adenocarcinoma cell line A549 (CCL-185) were purchased from the American Type Culture Collection (ATCC, Manassas, VA, USA). The BEAS-2B cells were cultured in 25 mM HEPESbuffered M199 medium containing 10% FBS, 2 mM L -glutamine, 100 U/ml penicillin, 100 mg/ml streptomycin supplemented with 2.5 mg/ml insulin, 361 ng/ml hydrocortisone, 2.5 mg/ml apotransferrin, and 20 ng/ml EGF [86]. The IMR90 cells were maintained in Eagle's MEM (EMEM, Lonza 125F) supplemented with 2 mM L -glutamine, 10% FBS and 1 mM sodium pyruvate with 100 U/ml penicillin and 100 mg/ml streptomycin.…”
Section: Cell Culturementioning
confidence: 99%